BREAST CANCER - Toshpulatova , L. (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
One of the many diseases in the field of oncology—due to the fact that breast cancer is common in women and the disease increases sharply, breast cancer is more common among men in recent times, besides that, explained by the fact that it is also used in young girls. In this article, we will look at the importance of screening programs and increases the effectivenesss of treatment based on the individual approach, the etio-pathogenesis of breast cancer, early diagnosis and treatment.